LncRNA PVT1 links estrogen receptor alpha and the polycomb repressive complex 2 in suppression of pro-apoptotic genes in hormone-responsive breast cancer - Viola Melone; Domenico Palumbo; Luigi Palo; Noemi Brusco; Annamaria Salvati; Antonietta Tarallo; Giorgio Giurato; Francesca Rizzo; Giovanni Nassa; Alessandro Weisz; Roberta Tarallo (Cell Death and Disease)
Abstract RNA-based therapeutics highlighted novel approaches to target either coding or noncoding molecules for multiple diseases treatment. In breast cancer (BC), a multitude of deregulated long noncoding RNAs (lncRNAs) have been identified as potential therapeutic targets also in the context of antiestrogen resistance, and the RNA binding activity of the estrogen receptor α (ERα) points additional potential candidates to interfere with estrogenic signaling. A set of lncRNAs was selected among ERα-associated RNAs in BC cell nuclei due to their roles in processes such as transcriptional regulation and epigenetic chromatin modifications. Native immunoprecipitation of nuclear ERα-interacting RNAs coupled to NGS (RIP-Seq) was performed in MCF-7 cells, leading to the identification of essential lncRNAs interacting with the receptor in multi-molecular regulatory complexes. Among these, PVT1, FGD5-AS1 and EPB41L4A-AS1 were selected for further investigation. Functional assays and transcriptome analysis following lncRNA knock-down indicated PVT1 as the master modulator of some of the most relevant BC hallmarks, such as cell proliferation, apoptosis, migration and response to hypoxia. In addition, targeted experiments identified PVT1 as a key factor in the composition of PRC2-ERα network involved in downregulation of tumor suppressor genes, including BTG2.